A simplified method for fatigue life evaluation of welded joints in OSD considering welding residual stress relaxation. (January 2023) - Zhong, Wen; Song, Yongsheng; Ding, Youliang; Fang, Zhao
Abstract: The welding residual stress at the welded joints of orthotropic steel decks (OSD) has a significant influence on the fatigue life, and welding residual stress relaxation (WRSR) occurs under vehicle loading. The existing fatigue evaluation method for steel bridges does not consider the WRSR on fatigue life and may cause a large deviation between the fatigue life prediction results and the fatigue cracking in the field. This paper proposes a simplified fatigue life evaluation method that can consider WRSR quantitatively. First, the initial welding residual stress (IWRS) distribution model is established based on residual stress tests and numerical simulation. Second, the simplified mechanical model of the coupled effect of IWRS and vehicle-induced structural stress as well as the law of WRSR are established via stress analysis at the weld toe section of DRWJs under external loading. Furthermore, the peak/valley value of the coupled effect of IWRS and vehicle-induced structural stress are determined, and a stress time-history simplification method considering WRSR is proposed. On this basis, a simplified fatigue life evaluation method considering the WRSR of DRWJs on OSDs is finally proposed and combined with the Q345 steel full-range SN curve model. The Jiangyin Yangtze River Highway Bridge is used as an example to demonstrate the fatigue life evaluation procedure of this proposed model in detail. Based on the multiscale finite element model (FEM) considering the coupling effect of the WRS and vehicle loading stress, the real stress time-history curves of DRWJs under vehicle loading cases are extracted and compared to those of the simplified method. Based on the full-range SN curve model considering IWRS and WRSR, the fatigue life of the welding joints of Jiangyin Bridge is finally calculated, and the results are more accurate and closer in value to the field observations of fatigue cracking when compared with the Eruocode3 standard. This provides a theoretical basis for fatigue analysis and lifetime assessment technology of large span highway steel box girder bridges.